2011
DOI: 10.1080/03235400903145558
|View full text |Cite
|
Sign up to set email alerts
|

Sources of resistance toExserohilum turcicum(Pass.) andPuccinia polysora(Underw.) incitant of Turcicum leaf blight and polysora rust of maize

Abstract: A study was carried out to identify the sources of resistance to Turcicum leaf blight (TLB) and polysora rust in maize. Sixty indigenous and exotic inbred lines were evaluated under artificial epiphytotic conditions at two identified hot spot locations, Almora and Nagenahalli. After two years continuous screening, a total of 20 inbred lines were identified as a sources of resistance at both the locations for TLB, whereas 10 inbred lines were identified resistant against Polysora rust at Nagenahalli. A clear cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…The use of resistant cultivars is the most effective, efficient, safe and practical method of obviating loss in crop yield. Inherent resistance or tolerance of crop plants to pathogens is the safest, economical and eco-friendly disease management approach to cope up with the problem [15]. SMH4 was observed to show resistance towards Turcicum leaf blight and common rust.…”
Section: Resultsmentioning
confidence: 99%
“…The use of resistant cultivars is the most effective, efficient, safe and practical method of obviating loss in crop yield. Inherent resistance or tolerance of crop plants to pathogens is the safest, economical and eco-friendly disease management approach to cope up with the problem [15]. SMH4 was observed to show resistance towards Turcicum leaf blight and common rust.…”
Section: Resultsmentioning
confidence: 99%
“…The use of resistant cultivars is the most effective, efficient, safe and practical method of obviating loss in crop yield. Inherent resistance or tolerance of crop plants to infection by the pathogen can most likely be a safe alternative and most economical and eco friendly disease management venture (Kumar et al, 2011). The benefit cost ratio was estimated by calculating total cost of cultivation and the net returns of both the varieties on hectare basis.…”
Section: Resultsmentioning
confidence: 99%
“…The study indicated that disease severity was always higher in Nagenahalli which appears to have a more conducive environment for disease development compared to Varanasi. Over-all more resistant inbreds (HKI-586, HUZM-53, CM-145, V-336, V-338, HKI-PC- [25] reported that virulence pattern of the TLB Pathogen from Almora changed, as inbreds CM 138, CML 235 and NAI 135, which showed a different resistant reaction over the two different locations. These results indicated changes in the virulence pattern of the pathogen as well as the impact of the environment.…”
Section: Discussionmentioning
confidence: 99%